A construção identitária de uma escola no sul de Minas Gerais: sendas percorridas - Ramos, Marcelino da Costa (2021)
This research, developed in the Professional Master's Degree in Education at the Federal University of Lavras, proposes to study and analyze the paths taken by a state school in the south of Minas Gerais, seeking to analyze its evolution as a teaching institution and the problems faced along this path towards construction. of your identity. Therefore, this study is based on the analysis of Brazilian educational legislation, in force from 1927, the year the school was created, to the present day, in a work that traces the history of this institution written by local historian. Along with its history, an attempt was made to analyze the history of education in Brazil, through the work carried out by ROMANELLI (1986), as well as studies on the pedagogical political project (Veiga, 2013; Vasconcellos, 2008). The research is characterized as qualitative research, focusing on document analysis (legislation and secondary source). In the development of the work, it was analyzed how the national educational legislation guided the national policy and reflected in the local policy, through the situations experienced by this school, which is believed to be not an isolated case, but which is repeated by other institutions causing uncertainties, as the closure scenario of this institution and others. This scenario made us realize that the creation of stronger and stronger bonds by the school community becomes an alternative of resistance, but these bonds can only be built through a political pedagogical project constituted in a democratic and participatory way, something that has been missing strength today. As a product of this master's degree, an elaboration work was elaborated on the Political Pedagogical Project, which will be delivered to the educational institution so that they can think about their actions and reinforce the construction of their identity.